Ucp1 Ablation Improves Skeletal Muscle Glycolytic Function in Aging Mice - Jin Qiu; Yuhan Guo; Xiaozhen Guo; Ziqi Liu; Zixuan Li; Jun Zhang; Yutang Cao; Jiaqi Li; Shuwu Yu; Sainan Xu; Juntong Chen; Dongmei Wang; et al. (Advanced Science)
Abstract Muscular atrophy is among the systematic decline in organ functions in aging, while defective thermogenic fat functionality precedes these anomalies. The potential crosstalk between adipose tissue and muscle during aging is poorly understood. In this study, it is showed that UCP1 knockout (KO) mice characterized deteriorated brown adipose tissue (BAT) function in aging, yet their glucose homeostasis is sustained and energy expenditure is increased, possibly compensated by improved inguinal adipose tissue (iWAT) and muscle functionality compared to age‐matched WT mice. To understand the potential crosstalk, RNA‐seq and metabolomic analysis were performed on adipose tissue and muscle in aging mice and revealed that creatine levels are increased both in iWAT and muscle of UCP1 KO mice. Interestingly, molecular analysis and metabolite tracing revealed that creatine biosynthesis is increased in iWAT while creatine uptake is increased in muscle in UCP1 KO mice, suggesting creatine transportation from iWAT to muscle. Importantly, creatine analog β‐GPA abolished the differences in muscle functions between aging WT and UCP1 KO mice, while UCP1 inhibitor α‐CD improved muscle glycolytic function and glucose metabolism in aging mice. Overall, these results suggested that iWAT and skeletal muscle compensate for declined BAT function during aging via creatine metabolism to sustain metabolic homeostasis.